Contract farming and rice production efficiency in Ghana. Issue 3 (29th April 2020) - Bidzakin, John Kanburi; Fialor, Simon C.; Awunyo-Vitor, Dadson; Yahaya, Iddrisu
Abstract : Purpose: Even though many studies identify positive effects of contract farming (CF) on the livelihood of farmers, the use of CF as a tool to increase farm performance is unsettled debate. Information on CF is relatively not available in staple food chains. Theoretical considerations have shown that there are challenges in employing CF in staple food chains such as rice. With the increasing trend of rice CF in Ghana, it is very critical to establish its performance in rice production in Ghana. It is therefore imperative to analyse the impact of CF on the performance of smallholder rice farmers. Design/methodology/approach: A survey was conducted where 350 rice farmers selected through a stratified sampling technique using structured questionnaires were interviewed. Descriptive and inferential statistics including stochastic frontier analyses and endogenous treatment effect regression were used to analyse the data. Findings: The results from the endogenous treatment effect regression model show that CF improves rice farmers' technical, allocative and economic efficiencies by 21, 23 and 26%, respectively. Farm size and CF were identified as common factors influencing technical, allocative and economic efficiency measures of the farmers positively. It further identified age of farmer, educational level and household labour as factors influencing farmers' participation in CF positively. Research limitations/implications: It is recommended that CF is a good tool to enhance rice production efficiency, and hence, farmers should be encouraged to participate in CF as strategy to enhance the local rice production in Ghana. Social implications: The outcome of this study has the potential to influence rice production in the country. The country is a net importer of rice and just about 35% self-sufficient in rice production. Originality/value: This study is the first to assess performance of CF in rice crop production in Ghana and also one of the few to use efficiency as a performance measure.